College sport and declining stadium attendance : designing adaptive strategies - Abeza, Gashaw; O'Reilly, Norm, 1973-; Kashuck, Kyle; Law, Joshua; Speck, Alexandra (London : Human Kinetics, Inc., 2018)
This case study presents the challenge of declining football attendance that a number of NCAA football programs are facing. The case participants (as members of a hypothetically formed advisory board) are asked to develop adaptive strategies and tactics to respond to this challenge by conducting an in-depth examination of fans' declining stadium attendance and proposing recommendations to the Pac-12 Commissioner's office. Particularly, students are expected to detail the reasons for fans' declining stadium attendance, to identify the short-term and long-term implications of declining stadium attendance, and to specify adaptive (corrective) strategies that can be designed based on Arizona State University's ticket-related marketing initiatives as a template. As a member of the advisory board, students are asked to address a list of questions and provide recommendations to address the challenge.
Originally Published InAbeza, G., O'Reilly, N., Kashuck, K., Law, J., & Speck, A. (2018). College Sport and Declining Stadium Attendance: Designing Adaptive Strategies. Case Studies in Sport Management, 7(1), 4–10.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sports administration; College sports -- Management; Sports spectators